2010
DOI: 10.1002/jbmr.89
|View full text |Cite
|
Sign up to set email alerts
|

Function of OPG as a traffic regulator for RANKL is crucial for controlled osteoclastogenesis

Abstract: The amount of the receptor activator of NF-kB ligand (RANKL) on the osteoblastic cell surface is considered to determine the magnitude of the signal input to osteoclast precursors and the degree of osteoclastogenesis. Previously, we have shown that RANKL is localized predominantly in lysosomal organelles, but little is found on the osteoblastic cell surface, and consequently, the regulated subcellular trafficking of RANKL in osteoblastic cells is important for controlled osteoclastogenesis. Here we have examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
41
0
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 48 publications
2
41
0
2
Order By: Relevance
“…Furthermore, we recently showed that osteoprotegerin (OPG) associates with RANKL in the Golgi apparatus and that the formation of this complex strengthens the interaction between RANKL and Vps33a, which results in the effective transport of newly synthesized RANKL to the lysosomes without transiting through the plasma membrane. (16) In OPGdeficient primary osteoblastic cells, the accumulation of RANKL at the Golgi apparatus correlated with an increase in the amount of RANKL that was leaked to the cell surface. (16) In vitro analyses using several OPG mutants revealed that the activity of OPG as a traffic regulator for RANKL requires the latter domain of OPG and is as important as the function of OPG as a decoy receptor for RANKL.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Furthermore, we recently showed that osteoprotegerin (OPG) associates with RANKL in the Golgi apparatus and that the formation of this complex strengthens the interaction between RANKL and Vps33a, which results in the effective transport of newly synthesized RANKL to the lysosomes without transiting through the plasma membrane. (16) In OPGdeficient primary osteoblastic cells, the accumulation of RANKL at the Golgi apparatus correlated with an increase in the amount of RANKL that was leaked to the cell surface. (16) In vitro analyses using several OPG mutants revealed that the activity of OPG as a traffic regulator for RANKL requires the latter domain of OPG and is as important as the function of OPG as a decoy receptor for RANKL.…”
Section: Introductionmentioning
confidence: 91%
“…(16) In vitro analyses using several OPG mutants revealed that the activity of OPG as a traffic regulator for RANKL requires the latter domain of OPG and is as important as the function of OPG as a decoy receptor for RANKL. (16) These facts strongly indicate that regulation of RANKL protein trafficking, especially the release of RANKL from secretory lysosomes, has a physiologic effect on osteoclastogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…However, the dogma that the balance between membrane-bound RANKL and secreted OPG decoy receptor as the mechanism underlying control of osteoclast differentiation and function is challenged by the elegant work of Masashi Honma, Hiroshi Suzuki, and colleagues presented in the current issue. (2) This work builds on previous studies by this same group demonstrating that the majority of newly synthesized RANKL in osteoblasts is not transported to the cell surface but shuttled from the Golgi apparatus to secretory lysosomes, where it is stored. (3) A small portion of RANKL is transported directly from the Golgi apparatus to the cell surface by what is referred by these authors to as the ''alternative pathway.''…”
mentioning
confidence: 52%
“…ST‐2 cells (a murine osteoblastic cell line [RIKEN, Ibaragi, Japan]), were maintained in α‐minimum essential medium (Sigma‐Aldrich) containing 10% fetal bovine serum (Moregate Biotech), penicillin (100 U/mL) and streptomycin (100 µg/mL) (Sigma‐Aldrich) 31, 32. After 12 hours of serum starvation, the cells were treated with vehicle or various concentrations of W9 or OP3‐4, as indicated, for 20 minutes.…”
Section: Methodsmentioning
confidence: 99%
“…After 12 hours of serum starvation, the cells were treated with vehicle or various concentrations of W9 or OP3‐4, as indicated, for 20 minutes. Total cell lysates were prepared and analyzed by Western blotting as described previously 31, 32. Briefly, ice‐cold PBS was used to stop the stimulation and the cells were immediately lysed lysis buffer (PBS, pH 7.4, 1.0% Triton X‐100) supplemented with protease inhibitors (Roche Diagnostics, Indianapolis, IN, USA) and phosphatase inhibitors (Sigma‐Aldrich).…”
Section: Methodsmentioning
confidence: 99%